Patient and Therapist Experiences of the SaeboFlex: A Pilot Study - Larissa Andriske; Debbie Verikios; Danielle Hitch (Hindawi-Wiley, 2017)
Objective. The aim of this pilot study was to explore the experiences of both patients and therapists of using the SaeboFlex. Method. A mixed methods approach was adopted. Patients completed a questionnaire which included the Psychosocial Impacts of Assistive Devices Scale (PIADS) (Version 3.0) and 6 qualitative questions. Therapists completed 2 qualitative questionnaires, which collected data on the regimen adopted for the SaeboFlex and reflections on their practice with this device. Results. The SaeboFlex had a mostly positive impact on both the psychosocial experience of patients and their ability to do, be, and become. Intervention regimens were broadly similar between therapists, and both patients and therapists stated that the SaeboFlex increased motivation for therapy. Conclusion. This study has added to our tentative understanding of the SaeboFlex, but more rigorous research is required to build a robust evidence base.